The Qur'an and Javanese Culture Acculturation: The Case of Jamasan Gong Kyai Pradah in Blitar District - Labib, Mohammad Mughni; Musolli, Musolli (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This research is motivated by the widespread belief and practice of traditional ceremonies such as the Jamasan Gong Kyai Pradah among the community. This phenomenon is intriguing to study, especially in the modern era where rationality predominates and such customs are gradually being supplanted by technology. The study examines the role of the Qur'an in the cultural acculturation of Javanese society through the Jamasan Gong Kyai Pradah tradition in Lodoyo Culture, Blitar District. The author uses a qualitative approach focusing on interaction analysis, and the research explores how the Quran influences and interprets this culturally and spiritually rich local context. The Jamasan Gong Kyai Pradah tradition uniquely synthesizes Islamic values and Javanese cultural heritage. The Qur'an serves as a spiritual guide in this ceremony and as a guardian and enhancer of religious identity and cultural values within the Lodaya community. The results demonstrate that the acculturation of Islamic teachings and Javanese traditions in Jamasan Gong Kyai Pradah enriches the understanding of religion and strengthens communal solidarity and collective identity. This study emphasizes the importance of cultural integration in religious contexts to preserve and develop rich local traditions. This article asserts that Jamasan Gong Kyai Pradah is a tangible example of how religion can synergize with culture in dynamic harmony. This integration not only enriches the community's spiritual life but also supports inclusive social development and fosters respect for cultural diversity in Indonesia.